TI-RICH PHLOGOPITE FROM MT. VULTURE (POTENZA, ITALY) INVESTIGATED BY A MULTIANALYTICAL APPROACH: SUBSTITUTIONAL MECHANISMS AND ORIENTATION OF THE OH DIPOLES - Scordari F.; Ventruti G.; Sabato A.; Bellatreccia F.; Ventura G.D.; Pedrazzi G. (My University, 2006)
Trioctahedral mica samples, collected at Cava St. Antonio (Mt. Vulture, Italy) were studied by combining electron-microprobe and C-H-N elemental analyses, single-crystal X-ray diffraction refinement, Mössbauer and Fourier transform infrared spectroscopies. Electron-microprobe analyses show the crystals to be quite homogeneous with TiO2 ~ 3 wt% and F ranging from 0.42 to 0.59 wt%. Quantitative analyses of H combined with ferric/ferrous ratios from Mössbauer data allowed reliable crystal-chemical formulae to be derived. The results suggest that the entry of both Ti4+ and Fe3+ in the structure occurs through R-oxy substitution mechanisms involving deprotonation at O(4). This inference is supported by X-ray structure-refinement results (notably the c cell-parameter, the off-centering of the M2 cation towards O(4), the bond-length distortions of the cis-M2 octahedron) obtained using anisotropic thermal parameters in space group C2/m. The amount of oxy-substitutions from both electron-microprobe and X-ray data is in agreement with carbon-hydrogen-nitrogen analyses which give an average anion composition (OH1.25O0.65F0.10). Polarized-light infrared spectroscopy shows a complex OH-stretching spectrum which is composed of several overlapping (at least five) components. These can be assigned to the main octahedral local configurations that are compatible with the chemical composition. Pleochroic Fourier transform infrared spectroscopy measurements done along the principal optical directions show that the O-H bond axis is tilted from [001] and provide the average orientation of the O-H dipole in the structure: O-H ^ α ~ 23 ° O-H ^ γ ~ 56°. © 2006 E. Schweizerbart'sche Verlagsbuchhandlung.
Keywords: C-H-N ELEMENTAL ANALYSIS; CRYSTAL CHEMISTRY; EMPA; MöSSBAUER; POLARIZED-LIGHT FTIR; SREF; TRIOCTAHEDRAL 1M-MICAS BEARING TITANIUM